2019
DOI: 10.1515/jpm-2019-0072
|View full text |Cite
|
Sign up to set email alerts
|

A 17-years analysis of terminations of pregnancy ≥14 weeks of gestation in a German level 1 perinatal center

Abstract: Background When discussing termination of pregnancy (TOP) after the first trimester, the main foci are the ethics and psychological reasoning/consequences. In daily clinical practice, physicians are often faced with affected women querying the frequency of their condition(s) and decisions made by women in similar situations. The present study aimed to provide an overview of a representable number of such cases. Methods Cases of TOP beyond 14 + 0 weeks of gestation were collected between January 2000 and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Kiver et al reported that chromosomal disorders (trisomy 21 with 15.5%) were the most common indication of TOP in 1746 cases terminated > 14 weeks for maternal and fetal indications [17]. In our study, we found similarly with previously reports that chromosomal disorders constitute the most common indication for TOP, followed by central nervous system abnormalities [9,[15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Kiver et al reported that chromosomal disorders (trisomy 21 with 15.5%) were the most common indication of TOP in 1746 cases terminated > 14 weeks for maternal and fetal indications [17]. In our study, we found similarly with previously reports that chromosomal disorders constitute the most common indication for TOP, followed by central nervous system abnormalities [9,[15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 92%
“…According to the German Federal Statistical Office data, the TOP rate has decreased in the last two decades, but there has been an increase in the termination rates above the viability limit. It was stated that only early screening of maternal and fetal conditions can considerably prevent pregnancy terminations above the viability limit [17]. Fetal viability is defined as the point at which the fetus can survive independently of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Next to very preterm birth and foetal growth restriction, congenital anomalies are the principal contributors to perinatal mortality 27 . However, because of the poor prognosis of the most severe anomalies and the risk of long‐term disability, the rates of termination of pregnancy are much higher in cases with congenital anomalies 31 …”
Section: Commentmentioning
confidence: 99%
“…27 However, because of the poor prognosis of the most severe anomalies and the risk of long‐term disability, the rates of termination of pregnancy are much higher in cases with congenital anomalies. 31 When parents opt for pregnancy continuation, delivery of affected newborns is scheduled in tertiary care centres with neonatal intensive care units where postnatal surgical correction of structural defects can take place. Indeed, neonatal surgery has been proven to be an effective strategy to considerably reduce neonatal deaths, especially in newborns with isolated abdominal wall, gastrointestinal, cardiac and diaphragmatic congenital defects.…”
Section: Commentmentioning
confidence: 99%
“…It also increases the safety of such procedures. Terminations performed later are usually due to structural fetal defects which develop at later stages of pregnancy [21]. In the second trimester, abortion may usually be performed for medical, social, or legal reasons [22].…”
Section: Legal Aspects Of Abortion In Restrictive Abortion Countriesmentioning
confidence: 99%